2019
DOI: 10.1002/jcop.22291
|View full text |Cite
|
Sign up to set email alerts
|

The life‐enhancing alcohol‐management program: Results from a 6‐month nonrandomized controlled pilot study assessing a community based participatory research program in housing first

Abstract: A 2‐arm, 6‐month, nonrandomized controlled pilot trial was conducted to test the initial effectiveness of the Life Enhancing Alcohol‐management Program (LEAP) as an adjunct to Housing First (HF; e.g., permanent supportive housing) on alcohol and quality‐of‐life (QoL) outcomes. The LEAP entails resident‐driven leadership opportunities, meaningful activities, and pathways to recovery aimed at reducing alcohol‐related harm and improving QoL. Data analyses were conducted to test between‐ and within‐subjects effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…This study is secondary to a larger parent study (N = 116) testing the effects of resident-driven programming in a Housing First setting on alcohol and quality-of-life outcomes (Clifasefi et al, 2020). Participants in this secondary study were 66 residents (n = 7; 10.6% female) of a Housing First program serving people experiencing chronic homelessness and AUD.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study is secondary to a larger parent study (N = 116) testing the effects of resident-driven programming in a Housing First setting on alcohol and quality-of-life outcomes (Clifasefi et al, 2020). Participants in this secondary study were 66 residents (n = 7; 10.6% female) of a Housing First program serving people experiencing chronic homelessness and AUD.…”
Section: Methodsmentioning
confidence: 99%
“…Findings showed that LEAP participants engaged in significantly more meaningful activities than participants who received services as usual in their Housing First settings during this time frame. Within-subjects analyses showed significant decreases in alcohol quantity and alcohol-related harm among LEAP participants (Clifasefi et al, 2020). Further, participants who attended a "high" level of LEAP activities (≥2 activities a month), reported drinking 16% less and experiencing 10% less alcohol-related harm for each month that passed compared to people who did not (0-2 activities throughout the entire program).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations